How do donors allocate funds to NGOs? Evidence from Uganda - Spiros Bougheas; Alessia Isopi; Trudy Owens (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2012)
We analyse the selectivity criteria used by institutional donors when they allocate funds to NGOs. A simple screening model predicts that donors who care more about efficiency will screen NGOs and concentrate their funding on those that operate accordingly while donors who care less about efficiency and more about local connections will not screen NGOs and disperse their funds independent of these criteria. We then test these predictions of the model using a unique survey data set of 412 NGOs in Uganda interviewed in two waves: 2002 and 2008. Our results indicate that local donors do not implement any selectivity criteria when allocating funds: what is of importance to them is how well connected the manager is locally, the geographic location of the NGO and whether the NGO is indigenous. This behaviour better fits with the interpretation that they are more interested in the ability of NGO to access beneficiaries. International donors, instead, when allocating funds rely more on characteristics that proxy the efficiency of both the NGO and the manager, including the manager's level of education, the appointment procedure, the external feedback on community needs, and whether the NGO respects or complies with monitoring and transparency procedures, such as being registered to pay taxes, or having their accounts audited. This behaviour is more consistent with that of a donor who cares about efficiency.
Keywords: F35; D82; 330; Funding Allocation; NGO